The Landscape for Institutional Investing in 2018 : Perspectives of Institutional Investors, An Input into the Investor Forum - World Bank Group (World Bank, Washington, DC, 2018)
The high-level Investor Forum will take place on November 29, 2018, in Buenos Aires, hosted by the President of Argentina, this year’s chair of the G20, and co-organized with the World Bank Group. The Forum will bring together leaders from the public sector and the global investment communityto explore how their combined power could contribute to sustained global economic growth andincrease the flow of long-term sustainable investments to where they are needed most. It is hopedthat the Forum will build strong momentum to support collaboration to address areas of shared interest, concern, and opportunity. As part of preparing for the Forum, the World Bank Group (WBG) conducted semi-structured interviews with senior executives—mostly chief executive officers and chief investment officers—in 34 global institutional investors, soliciting their views on the current operational and investment environment; strategic priorities going forward; and actionsrequired to scale up investments in sustainable, long-term projects, particularly investments in infrastructure. The major topics covered were (i) current perceptions regarding today’s economic and investment environments; (ii) mega-trends shaping existing and future investment strategies; (iii) sustainable investing along a number of dimensions; (iv) infrastructure investing; (v) investing in emerging markets; (vi) the potential role of the WBG and, by extension,other international financial institutions (IFIs); and (vii) their guidance on how to make the Forum a success. Given the geographic diversity, number, and level of seniority of the interviewed executives, we believe that these inputs can be considered a good reflection of views widely held by the global investment community. A key finding from the interviews was the significant degree of consensus among global investors on what were the principal concerns, opportunities, and actions needed.